Tree-based attributes of large trees more effectively regulate aboveground carbon stock than trait-based ones in temperate deciduous forests - Maryam Kazempour Larsary; Hassan Pourbabaei; Ali Salehi; Rasoul Yousefpour; Arshad Ali (Plant Diversity, 2025)
In forests, a few large trees (L-trees) versus small–medium trees (S-trees) are often considered the major reservoir of aboveground carbon stock (AGCS). Here, we hypothesize that tree species’ functional strategies regulate AGCS by tree sizes in temperate deciduous forests across local scale environmental gradients. Using data from 99 plots, we modelled the multivariate effects of the tree-based (tree diversity, stand density and multidimensional tree size inequality) versus the trait-based (multi-trait diversity and single-trait dominance) attributes of L-trees versus S-trees, along topographic and soil conditions, to predict AGCS through four L-trees threshold size (i.e., ≥ 50 cm fixed-diameter, top 95th percentile, ≥ top 50% cumulative AGCS descending-ranked ordered, and mean threshold size) approaches. The tree-based and trait-based attributes of L-trees and S-trees shaped species co-occurrence processes but L-trees regulated AGCS more effectively (31.29–93.20%) than S-trees and abiotic factors across four thereshold size approaches and two concepts. Although L-trees threshold size and tree-based attributes mattered for AGCS, the dominant resource-acquisitive strategy of structurally complex L-trees having higher specific leaf area but lower leaf dry matter content and lesser multi-trait dispersion could promote AGCS better than the resource-conservative strategy (low specific leaf area) of S-trees. Capturing tree species’ functional strategies, synergies and trade-offs across tree sizes can enhance our understanding of how to achieve nature-based carbon neutrality and lessen climate change. Thus, forest management and restoration initiatives should prioritize high-functioning tree species with dominant productive traits while conserving multi-trait diversified species in temperate deciduous forests.